GRAPHIC INTERPRETATION OF DIGITAL PRODUCTS AND APPLICATIONS IN STEGANOGRAPHY: GRAPHIC INTERPRETATION OF DIGITAL PRODUCTS AND APPLICATIONS IN STEGANOGRAPHY - Stoyanov, Emanuil; Stoyanov, Bozhidar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Today, the generation of digital data is easier than it has ever been. These are the so-called digitally born products – documents, images, audio and video recordings, software, e-books, digital models, maps, etc. They are more and more widely employed nowadays in a variety of fields, such as business, science, art, education, digital communications, national security, intelligence service, military science, etc. Their global application has brought forth the need for their being reliably protected and has made it an issue of paramount importance in the modern world of information. This necessity has imposed the fast development of two contemporary sciences - cryptography and steganography. The present report treats one of the recent variations in the development of steganography - digital steganography, suggesting a universal idea for its application to all types of digital products.